PENGARUH SANKSI PAJAK DAN TINGKAT KEPERCAYAAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI PADA KPP PRATAMA JAKARTA GAMBIR TIGA - Amelia Salma Nayla; Muhammad Firzah (Jurnal Ilmu Administrasi Publik, 2026)
The phenomenon of this study is the declining level of compliance among individual taxpayers at KPP Pratama Jakarta Gambir Tiga over the past few years. This decline in taxpayer compliance has negatively impacted state revenue from the tax sector. The factors considered to influence individual taxpayer compliance in this study are Tax Sanctions and Level of Trust. This study aims to analyze the effect of Tax Sanctions and Level of Trust on individual taxpayer compliance at KPP Pratama Jakarta Gambir Tiga. This study used a quantitative method with simple random sampling technique. The number of respondents in this study is 100 individual taxpayers registered at KPP Pratama Jakarta Gambir Tiga. Data were analyzed using the coefficient of determination test, t-test, and F-test using SPSS Version 30. The results indicate that Tax Sanctions have a positive and significant effect on individual taxpayer compliance, contributing 39,1%. Level of Trust also has a positive and significant effect on individual taxpayer compliance, with a contribution of 33,1%. Furthermore, Tax Sanctions and Level of Trust simultaneously have a positive and significant effect on individual taxpayer compliance at KPP Pratama Jakarta Gambir Tiga, with a combined contribution of 62,1%. Keywords Tax Sanctions, Trust Level, Taxpayer Compliance